The R136 star cluster dissected with Hubble Space Telescope/STIS: III. The most massive stars and their clumped winds - Brands, Sarah A.; de Koter, Alex; Bestenlehner, Joachim M.; Crowther, Paul A.; Sundqvist, Jon O.; Puls, Joachim; Caballero-Nieves, Saida M.; Abdul-Masih, Michael; Driessen, Florian A.; García, Miriam; Geen, Sam; Gräfener, Götz; et al. (Astronomy and astrophysics, 2022)
Methods. We simultaneously analyse optical and ultraviolet spectroscopy of 53 O-type and three WNh-stars using the FASTWIND model atmosphere code and a genetic algorithm. The models account for optically thick clumps and effects related to porosity and velocity-porosity, as well as a non-void interclump medium. - Results. We obtain stellar parameters, surface abundances, mass-loss rates, terminal velocities, and clumping characteristics and compare them to theoretical predictions and evolutionary models. The clumping properties include the density of the interclump medium and the velocity-porosity of the wind. For the ﬁrst time, these characteristics are systematically measured for a wide range of effective temperatures and luminosities. - Conclusions. We conﬁrm a cluster age of 1.0-2.5 Myr and derived an initial stellar mass of ≥250 M for the most massive star in our sample, R136a1. The winds of our sample stars are highly clumped, with an average clumping factor of fcl = 29 ± 15. We ﬁnd tentative trends in the wind-structure parameters as a function of the mass-loss rate, suggesting that the winds of stars with higher mass-loss rates are less clumped. We compare several theoretical predictions to the observed mass-loss rates and terminal velocities and ﬁnd that none satisfactorily reproduce both quantities. The prescription of Krticˇka & Kubát (2018) matches the observed mass-loss rates best.
Gesehen am 20.9.2022